Relationship of Supplement Intake Behavior to Performance and Grazing Behavior of Cattle Grazing Mixed-Grass Rangelands - Wyffels, Samuel A.; Dafoe, Julia M.; Parsons, Cory T.; Boss, Darrin L.; DelCurto, Timothy (Journal of Agricultural Studies, 2021)
This study evaluated the relationships between supplement intake behavior, beef cattle performance, and grazing behavior on dormant northern mixed-grass rangelands. In each of two years, a commercial herd of bred cows grazed a rangeland pasture from November to January. All cattle were managed as one contemporary group. Calf birth date, birth weight, and adjusted 205-day weaning weight were collected for each cow following the grazing season each year as cow performance metrics. During the grazing season, all cattle were provided free-choice access to a self-fed supplement. Supplement intake behavior was measured for each individual. Grazing behavior was monitored for 30 randomly selected individuals. The relationship of individual average daily supplement intake (R = 0.65; ρ = 0.65), supplement consumption rate (R = 0.58; ρ = 0.54), the coefficient of variation of supplement intake (R = 0.51; ρ = 0.50), and the amount of time spent at the feeder (R = 0.47; ρ = 0.49) were positively correlated and ranked across years (P < 0.01), suggesting individual animal supplement intake behavior is repeatable for cattle grazing dormant season rangelands. Additionally, there were multiple significant associations between supplement intake behavior, cattle performance, and grazing behavior (P ≤ 0.05); however, the majority were weak associations that accounted for minimal variation in cattle performance and grazing behavior (R ≤ 0.27; r2 ≤ 0.07). Although supplement intake behavioral traits were repeatable across years, its use as a metric to predict animal performance and grazing behavior may be limited.